Language awareness as a prerequisite of literacy skills - Anna Kucharská; Klára Špačková; Martina Šmejkalová (LingBaW)
Monitoring children’s language ability levels makes it possible to predict their school achievement and identify potential difficulties. Identifying literacy difficulties in terms of specific learning disabilities is an important topic for elementary school pupils. Today, there is a general consensus based on research evidence that the diagnostic battery of literacy skills should always include a test of language abilities, through which the prerequisites for individual reading skills and at-risk readers can be identified.